A high-voltage-resistant x8r multilayer ceramic capacitor, a preparation method thereof and a porcelain powder

CN122696535APending Publication Date: 2026-09-04HANGZHOU XINGRONG TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611160285.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-09-04

AI Technical Summary

Technical Problem

但过量Sr2+会导致室温介电常数大幅下降(通常低于2000),而含铅添加剂已受RoHS指令限制;Bi2O3虽能有效移峰,但易与BaTiO3发生过度反应形成非铁电第二相,导致介电损耗升高、绝缘电阻劣化

Benefits of technology

[0016] The positive effects of this invention are: the ceramic powder provided by this invention has high pressure resistance, high dielectric constant, excellent high temperature stability, and meets the EIA X8R standard.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122696535A_ABST
    Figure CN122696535A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of electronic ceramic materials and multilayer ceramic capacitors, and particularly relates to a high-voltage X8R multilayer ceramic capacitor and a preparation method and ceramic powder thereof. The high-voltage X8R multilayer ceramic capacitor comprises barium titanate, strontium carbonate, zirconium oxide, niobium oxide (Nb2O5), yttrium oxide, magnesium carbonate, manganese carbonate and lithium fluoride. The X8R multilayer ceramic capacitor provided by the application has high-voltage characteristics, high dielectric constant, excellent high-temperature stability and meets the EIA X8R standard.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of electronic ceramic materials and multilayer ceramic capacitors, specifically relating to a high voltage withstand characteristic X8R multilayer ceramic capacitor, its preparation method, and ceramic powder. Background Technology

[0002] With the accelerated industrialization of third-generation semiconductor materials (silicon carbide SiC and gallium nitride GaN) and the rapid development of fields such as new energy vehicles, oil well logging, and aerospace electronics, electronic systems are placing more stringent demands on passive components operating under high temperature, high voltage, and high power density environments. Multilayer ceramic capacitors (MLCCs), as the most widely used passive electronic components, have seen their operating temperature limit increased from the traditional 125℃ (X7R) to 150℃ (X8R), while simultaneously requiring stable capacitance output and extremely high insulation reliability under high DC bias field strength (≥40kV / cm).

[0003] Currently, ceramic dielectric materials meeting the X8R standard mainly employ barium titanate (BaTiO3)-based solid solution systems, achieved through A-site or B-site ion substitution (such as Sr...). 2+ Zr 4+ Ca 2+ To push the Curie temperature (Tc) to higher temperatures, composite doping with rare earth oxides (Y₂O₃, Dy₂O₃, Ho₂O₃, etc.) and acceptor additives (MnCO₃, MgCO₃, etc.) is used to broaden the dielectric temperature spectrum and suppress grain growth. However, existing technologies still have the following bottlenecks: First, there is a trade-off between high-temperature stability and dielectric constant. To raise the Curie temperature above 130°C, traditional methods often employ high Sr content... 2+ Replace Ba 2+ Alternatively, peak-shifting agents such as Bi2O3 and PbO can be added. However, excessive Sr... 2+This leads to a significant decrease in the room temperature dielectric constant (typically below 2000), while lead-containing additives are already restricted by the RoHS directive; although Bi2O3 can effectively shift peaks, it easily reacts excessively with BaTiO3 to form a non-ferroelectric second phase, resulting in increased dielectric loss and deteriorated insulation resistance. Second, the bottleneck of deteriorated DC bias characteristics. To achieve wide-temperature stability, X8R ceramics typically construct a core-shell structure of "ferroelectric core-paraelectric shell". However, traditional solid-state doping processes are difficult to achieve uniform distribution of doping elements, and rare earth ions are prone to enrichment at grain boundaries or the formation of local over-solid solution regions, resulting in uneven shell thickness and severe lattice mismatch at the core-shell interface. Under the action of a strong DC electric field, ferroelectric domain flipping is hindered, polarization saturation effect is aggravated, and capacitance decay often exceeds -40% (40kV / cm), severely restricting its application in high-voltage scenarios. Third, insufficient matching of base metal internal electrodes. To achieve cost reduction, X8R MLCCs generally use nickel as the internal electrode, requiring a reducing atmosphere (oxygen partial pressure) to be used. Sintering at (atm) is used to prevent Ni oxidation. However, high Curie temperature modification often requires the addition of dopants with high melting points and high chemical inertness (such as ZrO2 and Y2O3), forcing the sintering temperature to rise above 1260℃, close to the upper limit of the safe melting point window of Ni electrodes (Ni melting point 1453℃, industrially the sintering temperature is usually controlled ≤1250℃). Excessively high sintering temperatures not only increase energy consumption, but also easily lead to discontinuous and spheroidized internal electrodes, seriously reducing yield and reliability. Fourth, existing technologies do not pay enough attention to the "intermediate-assisted doping" strategy. Recent studies have shown that the solid solution behavior of rare earth ions in the BaTiO3 lattice is highly dependent on the diffusion path and reaction with the intermediate phase. When oxides such as Y2O3 and Dy2O3 are added directly, their reactivity with BaTiO3 is low, making it difficult to form a uniform shell solid solution; however, by using highly active nano-perovskite phases (such as CaTiO3 and SrTiO3) as "carriers" or "bridging sites", the lattice diffusion of rare earth ions can be significantly promoted.

[0004] To address the aforementioned issues, Chinese invention patent CN106348748A discloses a high-temperature X8R type ceramic capacitor dielectric material. This material achieves a medium-temperature sintering temperature of 1100–1190℃ by synthesizing a barium titanate and bismuth sodium titanate eutectic compound to increase the Curie temperature, and by adding a niobium-manganese-zinc-cobalt eutectic compound, a silicon-lithium eutectic compound, a boron-barium eutectic compound, and rare earth oxides. However, this technical solution still has the following shortcomings: firstly, its sintering atmosphere is air, which cannot meet the reducing atmosphere requirements of the base metal Ni internal electrode; secondly, the eutectic composition is complex. Alkali metal ions are prone to migration under strong electric fields, raising concerns about long-term reliability. Thirdly, no specific optimization of DC bias characteristics has been performed, and its capacitance stability under high voltage fields has not been reported. Chinese invention patent CN108129143A proposes a high-voltage X8R dielectric material, which improves its withstand voltage by adding a Bi-based pyrochlore phase. However, its Curie temperature is only increased to around 135℃, and its sintering temperature remains as high as 1260℃, indicating insufficient compatibility with Ni electrodes during co-firing.

[0005] In summary, existing X8R dielectric material systems cannot simultaneously meet the comprehensive requirements of high-temperature stability at 150℃, high withstand voltage of ≥55V / μm, and medium-temperature reduction sintering at ≤1240℃. Therefore, developing a novel X8R ceramic powder and its preparation method that combines high Curie temperature, high dielectric constant, excellent DC bias characteristics, and the ability to be co-fired with Ni electrodes at medium temperatures has significant academic value and urgent industrial demand. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides a high-voltage-resistance X8R multilayer ceramic capacitor, its preparation method, and ceramic powder. The X8R multilayer ceramic capacitor provided by this invention exhibits high voltage resistance, high dielectric constant, excellent high-temperature stability, and meets the EIA X8R standard.

[0007] The present invention solves the above-mentioned technical problems through the following technical solutions.

[0008] This invention provides a method for fabricating a high-voltage-resistance X8R multilayer ceramic capacitor, comprising the following steps: S1. Barium titanate, strontium carbonate, zirconium oxide, niobium oxide (Nb₂O₅), yttrium oxide, magnesium carbonate, manganese carbonate, and lithium fluoride are mixed and then ball-milled to obtain a uniform powder. S2. The powder is calcined in a muffle furnace to obtain ceramic powder. S3. The ceramic powder is obtained by mixing, granulating, shaping and sintering.

[0009] Optionally, in step S1, by weight, Based on the dosage, the amount of barium titanate added is 100 parts by weight, satisfying at least one of the following conditions: 1) The amount of strontium carbonate added is 1.5-3.5 parts by weight; for example, 2 parts by weight; 2) The amount of zirconium oxide added is 1.5-3.5 parts by weight; for example, 2.5 parts by weight; 3) The amount of niobium oxide added is 1-3 parts by weight; for example, 2 parts by weight; 4) The amount of yttrium oxide added is 0.5-2 parts by weight; for example, 1 part by weight; 5) The amount of magnesium carbonate added is 0.5-3 parts by weight; for example, 1.5 parts by weight. 6) The amount of manganese carbonate added is 0.5-1 parts by weight; for example, 0.5 parts by weight; 7) The amount of lithium fluoride added is 0.1-0.5 parts by weight; for example, 0.2 parts by weight.

[0010] Optionally, in step S1, by weight, Based on the dosage, the amount of barium titanate added is 100 parts by weight, the amount of strontium carbonate added is 1.5-3.5 parts by weight, the amount of zirconium oxide added is 1.5-3.5 parts by weight, the amount of niobium oxide added is 1-3 parts by weight, the amount of yttrium oxide added is 0.5-2 parts by weight, the amount of magnesium carbonate added is 0.5-3 parts by weight, the amount of manganese carbonate added is 0.5-1 parts by weight, and the amount of lithium fluoride added is 0.1-0.5 parts by weight.

[0011] Optionally, in step S1, by weight, Based on the dosage, the amount of barium titanate added is 100 parts by weight, the amount of strontium carbonate added is 2 parts by weight, the amount of zirconium oxide added is 2.5 parts by weight, the amount of niobium oxide added is 2 parts by weight, the amount of yttrium oxide added is 1 part by weight, the amount of magnesium carbonate added is 1.5 parts by weight, the amount of manganese carbonate added is 0.5 parts by weight, and the amount of lithium fluoride added is 0.2 parts by weight.

[0012] Optionally, in step S2, the calcination temperature in the muffle furnace is 800-1000℃, for example 950℃; and the calcination time in the muffle furnace is 2-8 hours, for example 3 hours.

[0013] This invention provides a high-voltage-resistance X8R ceramic powder prepared by the above-described method for preparing high-voltage-resistance X8R multilayer ceramic capacitors.

[0014] This invention provides a high-pressure-resistant X8R ceramic powder, which contains barium titanate, strontium carbonate, zirconium oxide, niobium oxide (Nb2O5), yttrium oxide, magnesium carbonate, manganese carbonate, and lithium fluoride.

[0015] Optionally, by weight, Based on the dosage, the amount of barium titanate added is 100 parts by weight, satisfying at least one of the following conditions: 1) The amount of strontium carbonate added is 1.5-3.5 parts by weight; for example, 2 parts by weight. 2) The amount of zirconium oxide added is 1.5-3.5 parts by weight; for example, 2.5 parts by weight. 3) The amount of niobium oxide added is 1-3 parts by weight; for example, 2 parts by weight. 4) The amount of yttrium oxide added is 0.5-2 parts by weight; for example, 1 part by weight. 5) The amount of magnesium carbonate added is 0.5-3 parts by weight; for example, 1.5 parts by weight. 6) The amount of manganese carbonate added is 0.5-1 parts by weight; for example, 0.5 parts by weight. 7) The amount of lithium fluoride added is 0.1-0.5 parts by weight; for example, 0.2 parts by weight.

[0016] The positive effects of this invention are: the ceramic powder provided by this invention has high pressure resistance, high dielectric constant, excellent high temperature stability, and meets the EIA X8R standard. Attached Figure Description

[0017] Figure 1 This is a dielectric constant-temperature characteristic curve of Embodiment 1 of the present invention.

[0018] Figure 2 This is a graph showing the rate of change of volumetric temperature and temperature characteristics of Embodiment 1 of the present invention.

[0019] Figure 3 This is a dielectric constant-temperature characteristic curve of Embodiment 2 of the present invention.

[0020] Figure 4 This is a graph showing the rate of change of volumetric temperature and temperature characteristics of Embodiment 2 of the present invention.

[0021] Figure 5 This is a dielectric constant-temperature characteristic curve of Embodiment 3 of the present invention.

[0022] Figure 6 This is a graph showing the rate of change of volumetric temperature and temperature characteristics of Embodiment 3 of the present invention.

[0023] Figure 7 This is a dielectric constant-temperature characteristic curve of Comparative Example 1 of the present invention.

[0024] Figure 8 This is a graph showing the rate of change of volumetric temperature versus temperature characteristic of Comparative Example 1 of the present invention.

[0025] Figure 9 This is a dielectric constant-temperature characteristic curve of Comparative Example 2 of the present invention.

[0026] Figure 10 This is a graph showing the rate of change of volumetric temperature versus temperature characteristic of Comparative Example 2 of the present invention.

[0027] Figure 11 This is a dielectric constant-temperature characteristic curve of Comparative Example 3 of the present invention.

[0028] Figure 12This is a graph showing the rate of change of volumetric temperature versus temperature characteristic of Comparative Example 3 of the present invention.

[0029] Figure 13 This is a superimposed graph of the dielectric constant-temperature characteristic curves of Examples 1-3 and Comparative Examples 1-3 of the present invention.

[0030] Figure 14 This is a superimposed graph of the volumetric temperature change rate-temperature characteristic curves of Examples 1-3 and Comparative Examples 1-3 of the present invention. Detailed Implementation

[0031] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions.

[0032] Example 1 Table 1

[0033] According to Table 1, barium titanate, strontium carbonate, zirconium oxide, yttrium oxide, magnesium carbonate, manganese carbonate, and lithium fluoride were weighed according to the weight ratio. After mixing, the mixture was ball-milled for 4 hours to obtain a uniform powder. The powder was dried and then calcined in a muffle furnace at 950℃ for 3 hours to obtain ceramic powder. The ceramic powder was then processed through main steps including mixing, granulation, blanking, and sintering to obtain X8R ceramic material with high pressure resistance.

[0034] The mixing process mainly involves grinding the calcined powder for another 6 hours. The granulation process involves mixing the powder with a 2.5% (w / w) polyvinyl alcohol (PVA) aqueous solution as a binder. The green body preparation process involves preparing a green body with a diameter of 20 mm and a thickness of 1 mm from the granulated powder under a pressure of 120 MPa. The sintering process involves embedding the green body, after debinding at 650 ℃, in an alumina powder corundum crucible, and then sintering it in a box-type resistance furnace at a temperature between 1200-1300 ℃ (below 1200 ℃, the ceramic material is under-fired; above 1300 ℃, the failure rate increases significantly), with a holding time of 4 hours.

[0035] The ceramic powder prepared in this embodiment was subjected to performance tests: the dielectric constant and loss (1 kHz, 1 Vrms) were measured using an LCR meter; the capacitance change rate from -55℃ to 150℃ was measured according to the EIA X8R standard; and the DC bias characteristics and breakdown field strength were measured using a Keithley 2410 high-voltage source meter. Test results: room temperature dielectric constant εr = 2380 (e.g., ...). Figure 1 As shown in the figure, dielectric loss tanδ = 1.6%, insulation resistivity ρv = 3.2 × 10⁻⁶. 12Ω·cm, Curie temperature Tc=144℃, volume change rate TCC=±7.7% (e.g., -55℃~150℃) Figure 2 As shown in the figure, the capacitance change rate ΔC / C under a DC bias of 40kV / cm is -23.5%, and the breakdown field strength Eb is 58 V / μm.

[0036] Example 2

[0037] Table 2

[0038] According to Table 2, barium titanate, strontium carbonate, zirconium oxide, yttrium oxide, magnesium carbonate, manganese carbonate, and lithium fluoride were weighed according to the weight ratio. After mixing, the mixture was ball-milled for 4 hours to obtain a uniform powder. The powder was dried and then calcined in a muffle furnace at 950℃ for 3 hours to obtain ceramic powder. The ceramic powder was then processed through main steps including mixing, granulation, blanking, and sintering to obtain X8R ceramic material with high pressure resistance.

[0039] The mixing process mainly involves grinding the calcined powder for another 6 hours. The granulation process involves mixing the powder with a 2.5% (w / w) polyvinyl alcohol (PVA) aqueous solution as a binder. The green body preparation process involves preparing a green body with a diameter of 20 mm and a thickness of 1 mm from the granulated powder under a pressure of 120 MPa. The sintering process involves embedding the green body, after debinding at 650 ℃, in an alumina powder corundum crucible, and then sintering it in a box-type resistance furnace at a temperature between 1200-1300 ℃ (below 1200 ℃, the ceramic material is under-fired; above 1300 ℃, the failure rate increases significantly), with a holding time of 4 hours.

[0040] The ceramic powder prepared in this embodiment was subjected to performance testing: room temperature dielectric constant εr = 2251 (e.g., Figure 3 As shown), dielectric loss tanδ=1.9%, insulation resistivity ρv=2.1×10¹² Ω·cm, Curie temperature Tc=148℃, capacitance change rate TCC=±8.6% from -55℃ to 150℃ (as shown). Figure 4 As shown in the figure, the capacitance change rate ΔC / C under a DC bias of 40kV / cm is -26.1%, and the breakdown field strength Eb is 55 V / μm.

[0041] Example 3

[0042] Table 3

[0043] According to Table 3, barium titanate, strontium carbonate, zirconium oxide, yttrium oxide, magnesium carbonate, manganese carbonate, and lithium fluoride were weighed according to the weight ratio. After mixing, the mixture was ball-milled for 4 hours to obtain a uniform powder. The powder was dried and then calcined in a muffle furnace at 950℃ for 3 hours to obtain ceramic powder. The ceramic powder was then processed through main processes such as mixing, granulation, blanking, and sintering to obtain X8R ceramic material with high pressure resistance.

[0044] The mixing process mainly involves grinding the calcined powder for another 6 hours. The granulation process involves mixing the powder with a 2.5% (w / w) polyvinyl alcohol (PVA) aqueous solution as a binder. The green body preparation process involves preparing a green body with a diameter of 20 mm and a thickness of 1 mm from the granulated powder under a pressure of 120 MPa. The sintering process involves embedding the green body, after debinding at 650 ℃, in an alumina powder corundum crucible, and then sintering it in a box-type resistance furnace at a temperature between 1200-1300 ℃ (below 1200 ℃, the ceramic material is under-fired; above 1300 ℃, the failure rate increases significantly), with a holding time of 4 hours.

[0045] The ceramic powder prepared in this embodiment was subjected to performance testing: room temperature dielectric constant εr = 2603 (e.g., Figure 5 As shown), dielectric loss tanδ=1.7%, insulation resistivity ρv=1.8×10¹² Ω·cm, Curie temperature Tc=142℃, capacitance change rate TCC=±11.6% from -55℃ to 150℃ (as shown). Figure 6 As shown in the figure, the capacitance change rate ΔC / C under a DC bias of 40kV / cm is -24.8%, and the breakdown field strength Eb is 56 V / μm.

[0046] Comparative Example 1 Table 4

[0047] According to Table 4, barium titanate, strontium carbonate, zirconium oxide, yttrium oxide, magnesium carbonate, and manganese carbonate were weighed according to the weight ratio. After mixing, the mixture was ball-milled for 4 hours to obtain a uniform powder. After drying, the powder was calcined in a muffle furnace at 950℃ for 3 hours to obtain ceramic powder. The ceramic powder was then processed through main processes such as mixing, granulation, blanking, and sintering to obtain X8R ceramic material with high pressure resistance.

[0048] The mixing process mainly involves grinding the calcined powder for another 6 hours. The granulation process involves mixing the powder with a 2.5% (w / w) polyvinyl alcohol (PVA) aqueous solution as a binder. The green body preparation process involves preparing a green body with a diameter of 20 mm and a thickness of 1 mm from the granulated powder under a pressure of 120 MPa. The sintering process involves embedding the green body, after debinding at 650 ℃, in an alumina powder corundum crucible, and then sintering it in a box-type resistance furnace at a temperature between 1200-1300 ℃ (below 1200 ℃, the ceramic material is under-fired; above 1300 ℃, the failure rate increases significantly), with a holding time of 4 hours.

[0049] The ceramic powder prepared in this embodiment was subjected to the following: room temperature dielectric constant εr = 2358 (e.g., Figure 7 As shown), dielectric loss tanδ=2.5%, insulation resistivity ρv=8.5×10¹¹ Ω·cm, Curie temperature Tc=131℃, capacitance change rate TCC=±48.9% (as shown). Figure 8 As shown in the figure, the capacitance change rate ΔC / C under a DC bias of 40kV / cm is -35.2%, and the breakdown field strength Eb is 46V / μm.

[0050] Comparative Example 2 Table 5

[0051] According to Table 5, barium titanate, strontium carbonate, zirconium oxide, yttrium oxide, magnesium carbonate, manganese carbonate, and lithium fluoride were weighed according to the weight ratio. After mixing, the mixture was ball-milled for 4 hours to obtain a uniform powder. The powder was dried and then calcined in a muffle furnace at 950℃ for 3 hours to obtain ceramic powder. The ceramic powder was then processed through main processes such as mixing, granulation, blanking, and sintering to obtain X8R ceramic material with high pressure resistance.

[0052] The mixing process mainly involves grinding the calcined powder for another 6 hours. The granulation process involves mixing the powder with a 2.5% (w / w) polyvinyl alcohol (PVA) aqueous solution as a binder. The green body preparation process involves preparing a green body with a diameter of 20 mm and a thickness of 1 mm from the granulated powder under a pressure of 120 MPa. The sintering process involves embedding the green body, after debinding at 650 ℃, in an alumina powder corundum crucible, and then sintering it in a box-type resistance furnace at a temperature between 1200-1300 ℃ (below 1200 ℃, the ceramic material is under-fired; above 1300 ℃, the failure rate increases significantly), with a holding time of 4 hours.

[0053] The ceramic powder prepared in this embodiment was subjected to performance testing: room temperature dielectric constant εr = 2377 (e.g., Figure 9As shown), dielectric loss tanδ=2.2%, insulation resistivity ρv=6.3×10¹¹ Ω·cm, Curie temperature Tc=140℃, capacitance change rate TCC=±28.2% from -55℃ to 150℃ (as shown). Figure 10 As shown in the figure, the capacitance change rate ΔC / C under a DC bias of 40kV / cm is -41.0%, and the breakdown field strength Eb is 42 V / μm.

[0054] Comparative Example 3 Table 6

[0055] According to Table 6, barium titanate, strontium carbonate, zirconium oxide, yttrium oxide, magnesium carbonate, manganese carbonate, and lithium fluoride were weighed according to the weight ratio. After mixing, the mixture was ball-milled for 4 hours to obtain a uniform powder. The powder was dried and then calcined in a muffle furnace at 950℃ for 3 hours to obtain ceramic powder. The ceramic powder was then processed through main processes such as mixing, granulation, blanking, and sintering to obtain X8R ceramic material with high pressure resistance.

[0056] The mixing process mainly involves grinding the calcined powder for another 6 hours. The granulation process involves mixing the powder with a 2.5% (w / w) polyvinyl alcohol (PVA) aqueous solution as a binder. The green body preparation process involves preparing a green body with a diameter of 20 mm and a thickness of 1 mm from the granulated powder under a pressure of 120 MPa. The sintering process involves embedding the green body, after debinding at 650 ℃, in an alumina powder corundum crucible, and then sintering it in a box-type resistance furnace at a temperature between 1200-1300 ℃ (below 1200 ℃, the ceramic material is under-fired; above 1300 ℃, the failure rate increases significantly), with a holding time of 4 hours.

[0057] The ceramic powder prepared in this embodiment was subjected to performance testing: room temperature dielectric constant εr = 2291 (e.g., Figure 11 As shown), dielectric loss tanδ=2.8%, insulation resistivity ρv=4.2×10¹¹ Ω·cm, Curie temperature Tc=125℃, capacitance change rate TCC=±21.6% from -55℃ to 150℃ (as shown). Figure 12 (As shown) (150℃ is beyond its operating range), the capacitance change rate ΔC / C under a DC bias of 40kV / cm is -48.5%, and the breakdown field strength Eb is 38 V / μm.

[0058] Performance Summary Analysis The dielectric properties, pressure resistance and sintering temperature of the ceramic powders prepared in Examples 1-3 and Comparative Examples 1-3 are summarized in Table 7.

[0059] Table 7 Performance Comparison of Various Examples and Comparative Examples

[0060] As can be seen from Table 7, the X8R ceramic powder prepared in the embodiments of the present invention is significantly superior to the comparative example in terms of Curie temperature, dielectric constant, dielectric loss, insulation resistance, high temperature stability and DC bias characteristics.

[0061] Specifically: For ease of comparison, the dielectric constant test results of Examples 1-3 and Comparative Examples 1-3 are superimposed as follows: Figure 13 As shown, the temperature change rate (TCC) test results of Examples 1-3 and Comparative Examples 1-3 are superimposed as follows: Figure 14 As shown.

[0062] The Curie temperatures of Examples 1 to 3 all reached above 142°C, which is 10 to 23°C higher than the comparative example, meeting the requirements for high-temperature applications at 150°C; the dielectric constant was ≥2250, which is more than 15% higher than the comparative example; the dielectric loss was ≤1.9%; and the insulation resistivity was improved by an order of magnitude; the capacitance change rate at 150°C was ≤±11.6%, which is far better than the ±21.6% to ±48.9% of the comparative example; the capacitance change rate under a DC bias of 40kV / cm was ≤-26.1%, which is more than 40% better than the comparative example; and the sintering temperature was as low as 1190 to 1220°C, which allows for good co-firing with the nickel internal electrode.

[0063] As can be seen from Example 1 and Comparative Example 1, without the addition of LiF, the above formulation is in a state of underburning at 1220°C, which does not meet the X8R standard.

[0064] In summary, this invention successfully fabricates high-voltage, high-stability X8R multilayer ceramic capacitors by introducing strontium carbonate and zirconium oxide as Curie temperature regulators, niobium pentoxide, yttrium oxide, magnesium carbonate, and manganese carbonate to synergistically construct a gradient shell structure, and using LiF as a sintering aid. The materials of this invention possess excellent comprehensive properties, and the fabrication process is compatible with existing multilayer ceramic capacitor production lines, making it suitable for large-scale industrial production and yielding significant economic and social benefits.

[0065] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made by those skilled in the art without departing from the concept and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a high-voltage-resistance X8R multilayer ceramic capacitor, characterized in that, It includes the following steps: S1. Barium titanate, strontium carbonate, zirconium oxide, niobium oxide, yttrium oxide, magnesium carbonate, manganese carbonate, and lithium fluoride are mixed and then ball-milled to obtain a uniform powder. S2. The powder is calcined in a muffle furnace to obtain ceramic powder. S3. The ceramic powder is obtained by mixing, granulating, shaping and sintering.

2. The method for preparing the X8R multilayer ceramic capacitor as described in claim 1, characterized in that, The amount of strontium carbonate added is 1.5-3.5 parts by weight.

3. The method for preparing the X8R multilayer ceramic capacitor as described in claim 1, characterized in that, The amount of zirconium oxide added is 1.5-3.5 parts by weight.

4. The method for preparing the X8R multilayer ceramic capacitor as described in claim 1, characterized in that, The amount of niobium oxide added is 1-3 parts by weight.

5. The method for preparing the X8R multilayer ceramic capacitor as described in claim 1, characterized in that, The amount of yttrium oxide added is 0.5-2 parts by weight.

6. The method for preparing the X8R multilayer ceramic capacitor as described in claim 1, characterized in that, The amount of lithium fluoride added is 0.1-0.5 parts by weight.

7. The method for preparing the X8R multilayer ceramic capacitor as described in claim 1, characterized in that, In step S1, by weight, Based on the dosage, the amount of barium titanate added is 100 parts by weight, the amount of strontium carbonate added is 1.5-3.5 parts by weight, the amount of zirconium oxide added is 1.5-3.5 parts by weight, the amount of niobium oxide added is 1-3 parts by weight, the amount of yttrium oxide added is 0.5-2 parts by weight, the amount of magnesium carbonate added is 0.5-3 parts by weight, the amount of manganese carbonate added is 0.5-1 parts by weight, and the amount of lithium fluoride added is 0.1-0.5 parts by weight.

8. The method for preparing the X8R multilayer ceramic capacitor as described in claim 1, characterized in that, In step S2, the calcination temperature in the muffle furnace is 800-1000℃; the calcination time in the muffle furnace is 2-8 hours.

9. A multilayer X8R ceramic capacitor prepared by the method of any one of claims 1-8.

10. A high-pressure-resistant X8R ceramic powder, comprising barium titanate, strontium carbonate, zirconium oxide, niobium oxide, yttrium oxide, magnesium carbonate, manganese carbonate, and lithium fluoride.

Citation Information

Patent Citations

  • High-temperature X8R type ceramic-capacitor dielectric material and preparation method thereof

    CN106348748A

  • High-superposition-characteristic wide-temperature-range low-power-consumption manganese-zinc soft magnetic ferrite and preparation method thereof

    CN108129143A